2018
DOI: 10.1063/1.5024914
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence threshold selection for obtaining robust recurrence characteristics in different embedding dimensions

Abstract: The appropriate selection of recurrence thresholds is a key problem in applications of recurrence quantification analysis and related methods across disciplines. Here, we discuss the distribution of pairwise distances between state vectors in the studied system's state space reconstructed by means of time-delay embedding as the key characteristic that should guide the corresponding choice for obtaining an adequate resolution of a recurrence plot. Specifically, we present an empirical description of the distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 30 publications
0
49
0
1
Order By: Relevance
“…It should be noted that the CCNDs derived from different time series tended to saturate for the high-dimensional recurrence network. This is because higher-dimensional recurrence networks change fewer and fewer of the distance values between the nodes [ 24 ], which was also observed in numerical investigations associated with the false nearest neighbor method [ 32 ]. In addition, the saturation behavior observed was also partially the result of the finite sample size.…”
Section: Analysis Of Synthetic Datamentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that the CCNDs derived from different time series tended to saturate for the high-dimensional recurrence network. This is because higher-dimensional recurrence networks change fewer and fewer of the distance values between the nodes [ 24 ], which was also observed in numerical investigations associated with the false nearest neighbor method [ 32 ]. In addition, the saturation behavior observed was also partially the result of the finite sample size.…”
Section: Analysis Of Synthetic Datamentioning
confidence: 98%
“…Several strategies for the selection of the threshold have been proposed. It was suggested that choosing a fixed link density is helpful for the estimation of the dynamical properties in many systems [ 23 , 24 , 25 ]. Therefore, we determined the threshold for the L -dimensional recurrence network, Δ L , by setting a fixed link density, ρ L , which is defined as follows: …”
Section: Network Construction From Time Seriesmentioning
confidence: 99%
“…Although in the literature, many approaches have been proposed for the selection of m and τ (Fraser, 1986;Albano et al, 1987;Kennel et al, 1992;Kaplan, 1993; Chun-Hua and Xin-Bao, 2004), we computed embedding dimension, m, as the first minimum of the false nearest neighbors function over the possible dimensions from zero to ten. An embedding dimension of m = 4 was obtained (Stephen et al, 2009;Kraemer et al, 2018) (see Figure 5 as en example of the m computation). Furthermore, Time delay τ was computed as the first minimum of the mutual information profile, maximizing the independence among the components of the embedding vector (see Figure 6 as an example of the τ computation).…”
Section: Phase-space (Ps) and Phase Space Reconstructionmentioning
confidence: 99%
“…The similarity threshold, ǫ, is a parameter that determines whether vectors in the phase space are identified as recurrent, i.e., as revisiting the same area of the phase space. Choosing an appropriate value for ǫ can be difficult [34] and investigating the impact of ǫ on RQA output is an active research topic [35,36]; in the present work, we use a nearest neighbor approach that does not require an explicit ǫ to be set.…”
Section: Jrqamentioning
confidence: 99%